Examining Crisis Preparedness in Higher Education Institutions: The Case of the COVID-19 Pandemic - Öztürk, Cebrail; Arabacı, İmam Bakır (Bolu Abant Izzet Baysal University, 2025)
The study aims to evaluate whether higher education institutions were prepared for the crisis caused by the Covid-19 pandemic and to assess the implementation of these preparations based on participants' perspectives. The research employs a qualitative design and is conducted using the case study method. The study group consists of participants selected through maximum variation and criterion sampling methods, including academic staff, administrators, administrative personnel, and students working in higher education institutions during the 2022-2023 academic year. Data for the study were collected using a semi-structured interview form and analyzed through content analysis. The findings indicate that institutional preparedness for managing the crisis caused by the Covid-19 pandemic played a significant role in preventing the crisis and minimizing the extent of its impact on institutions. It was particularly observed that preparedness for remote education processes and the necessary technological infrastructure had a critical influence in mitigating the effects of the crisis.

Araştırmada, Covid-19 salgınında ortaya çıkan kriz durumuna yükseköğretim kurumlarının hazırlıklı olup olmadığını ve yapılan hazırlıkların uygulamaya dönüştürülmesinin katılımcı görüşlerine göre değerlendirilmesini amaçlamaktadır. Çalışma, nitel araştırma olup durum analizi tekniğiyle yürütülmüştür. Çalışma grubu, 2022-2023 eğitim öğretim yılında yükseköğretim kurumlarında görev yapan akademik personel, yönetici, idari personel ve öğrencilerden maksimum çeşitlilik ve ölçüt örnekleme yöntemiyle seçilmiş katılımcılardan oluşmaktadır. Araştırmanın verileri yarı yapılandırılmış görüşme formu aracılığıyla toplanmıştır. Veriler içerik analizi yöntemiyle analiz edilmiştir. Araştırmanın sonucunda, Covid 19 salgınından kaynaklı krizin yönetilmesinde kurumların hazırlıklı olmasının krizi önlemede ve kuruma verdiği hasarın büyüklüğünde önemli bir etkiye sahip olduğu sonucuna varılmıştır. Kriz sürecinde özellikle kurumun uzaktan eğitim sürecine ve gerekli teknolojik altyapı konusunda hazırlıklı olması, krizin teğet geçmesinde önemli etkide bulunduğu anlaşılmıştır.
Yükseköğretim Kurumlarında Krizlere Hazırlık Durumlarının İncelenmesi (Covid-19 Salgını Örneği)
Keywords: Education Management; Eğitim Yönetimi